DEVELOPING ENGLISH LEARNING MATERIALS FOR HOUSEKEEPING FOR ELEVENTH-GRADE STUDENTS IN FIRST SEMESTER AT SMKN 1 SINGARAJA - Paramitha, Ida Ayu Putu Cintya; Wedhanti, Nyoman Karina; Mahendrayana, Gede (Universitas Suryakancana, 2023)
The implementation of this research aims to develop a textbook for English for Housekeeping for grade XI semester 1, majoring in hospitality at SMKN 1 Singaraja, Buleleng. English subject used in schools is still general, did not specific based on each student's major yet, and there was no learning material in accordance with the Merdeka Curriculum. The research method used is Design and Development (D&D) by Richey and Klein (2009) in Sugiyono (2017), in which there are three stages, namely Planning, Production, and Evaluation. The data analysis technique in this study uses with qualitative and quantitative methods. Â Based on the data, it was found that teachers and students need specific English with the hospitality major and an interesting English textbooks for Housekeeping. There are three learning units developed using Hutchinson and Waters' (1987) theory, namely 1) Provision and Preparation for Housekeeping Services, 2) Public Area Section, and 3) Handling Lost and Found for Guests. The results of this study are the English Textbook for Housekeeping which was evaluated by the two previous experts using a checklist questionnaire by Lizt (2005) on a Lickert scale. From the results of the expert's evaluation, calculated using the percentage formula and the Mean by Suharto (2006), it was known that the quality of the textbook English for Housekeeping is in the very good category based on the range of assessments by Suharto (2006). Therefore, this textbook can be used by teachers and students to explore English material, especially for Housekeeping subjects